Optimising sintering parameters on the characteristic of injection moulded 316L stainless steel utilising water soluble system / Nurul Farhana Omar ... [et al.] - Omar, Nurul Farhana; Wahab, Nor’Aini; Ahmad, Ismail Nasirudin; Sulong, Nurulsaidatulsyida (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
This paper describes an optimising sintering process in metal injection molding (MIM) of 316L SS employing a binder system consisting of palm stearin (PS), stearic acid (SA), polyethylene (PE) and thermoplastic rice starch (TPRS).